The Universal Declaration of Human Rights at 70: A time to look back, and a time to look forward - O'Regan, C (British Academy, 2018)
Anxiety about the future of democracy and human rights is widespread. To provide a framework within which to assess that anxiety, this article explores the history of the Universal Declaration of Human Rights, which was adopted seventy years ago by the General Assembly. The article outlines the traditional, rather whiggish, account of that history, which asserts that the project of proclaiming and protecting human rights in international law has seen steady improvement and expansion since 1948. The article argues that this account is at least partly misleading and that the history of the international human rights project since 1948 has been more complex, contingent and uneven. The article concludes by suggesting that recognising that the history of the international human rights project has been beset by difficulties and uncertainties may make it easier both to assess—and respond to—contemporary challenges.